2021
DOI: 10.3390/ijms22095028
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 Responses in the Cerebellum Lobules VI, VII, VIII Using Electroacupuncture Treatment for Chronic Pain and Depression Comorbidity in a Murine Model

Abstract: Depression is a prominent complex psychiatric disorder, usually complicated through expression of comorbid conditions, with chronic pain being among the most prevalent. This comorbidity is consistently associated with a poor prognosis and has been shown to negatively impact patient outcomes. With a global rise in this condition presenting itself, the importance of discovering long-term, effective, and affordable treatments is crucial. Electroacupuncture has demonstrated renowned success in its use for the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 66 publications
0
13
1
Order By: Relevance
“…Recent evidence from animal experiments has shown the neuroanatomical basis of ST36 in driving the vagal-adrenal axis, thus modulating anti-inflammatory responses in mice (12). Research in healthy individuals demonstrated the effects of ST36 in the somatosensory and motor areas, cerebellum, and limbic system (13,14). A meta-analysis on block-design fMRI, including both patients and healthy individuals, demonstrated that acupuncture at ST36 with deqi sensation exclusively activates the right hemisphere of the brain, such as the right orbital part of the inferior frontal gyrus (IFG), right median cingulate, and paracingulate gyri, right supramarginal gyrus, and pons (15).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence from animal experiments has shown the neuroanatomical basis of ST36 in driving the vagal-adrenal axis, thus modulating anti-inflammatory responses in mice (12). Research in healthy individuals demonstrated the effects of ST36 in the somatosensory and motor areas, cerebellum, and limbic system (13,14). A meta-analysis on block-design fMRI, including both patients and healthy individuals, demonstrated that acupuncture at ST36 with deqi sensation exclusively activates the right hemisphere of the brain, such as the right orbital part of the inferior frontal gyrus (IFG), right median cingulate, and paracingulate gyri, right supramarginal gyrus, and pons (15).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we established an inflammation-induced depression model and measured depression-like behaviors, inflammatory cytokines, glutamate level, and kynurenine metabolisms to find to measure the function of EA on depression. We observed EA could treat pathological inflammation ( Zhang et al, 2015 ), and as observed in the tail suspension test (TST) and forced swimming test (FST) behavioral responses, EA significantly attenuated depressive behavior ( Lottering and Lin, 2021 ). Moreover, in the nervous system, EA could ameliorate glutamate and regulate kynurenine metabolisms.…”
Section: Introductionmentioning
confidence: 95%
“…Meanwhile, stimulation at acupoints could lead to a multi-targeted effect on the central nervous system. For example, after stimulation at ST36, the changes of TRPV channels in the spinal cord ( Yang et al, 2017 ); cerebellum lobules V, VIa, VI, VII, and VIII ( Inprasit and Lin, 2020 ; Lottering and Lin, 2021 ); hippocampus; periaqueductal gray; and medial prefrontal cortex ( Lin et al, 2020 ) could be observed.…”
Section: Acupuncture Affects Transient Receptor Potential Vanilloid C...mentioning
confidence: 99%
“…Phosphorylation of downstream molecules was widely found after acupuncture-regulated TRPV channels ( Inprasit et al, 2018 ). Inprasit and Lin (2020) and Lottering and Lin (2021) performed a series of studies to clarify the role of acupuncture and TRPV in the cerebellum lobules. Both complete Freund’s adjuvant (CFA) and acid saline (AS) could lead to chronic pain, but the expression of TRPV1 in the cerebellum lobules is completely opposite.…”
Section: Acupuncture and Transient Receptor Potential Vanilloid Chann...mentioning
confidence: 99%